The Relationship Between Competitive Advantage, Customer Focus Strategy, And Customer Satisfaction In The Service Industry - Ravindra Safitra Hidayat; Selamat Riyadi; Heru Nugroho; Dadet Sugiarto (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study explores the intricate interplay between competitive advantage, customer focus strategies, and customer satisfaction within the service industry, emphasizing a human-centered approach to organizational development. Through a comprehensive literature review, the research highlights the transformative potential of aligning strategic initiatives with human values and emotional resonance. It underscores the importance of cultivating meaningful relationships with customers to create sustainable competitive advantages that extend beyond traditional economic metrics. The findings reveal that customer satisfaction is deeply rooted in both functional service excellence and emotional connections. By leveraging insights from customer experiences, organizations can design tailored strategies that resonate with individual needs and aspirations. Furthermore, the research demonstrates how customer-centric approaches influence broader organizational culture, fostering environments that prioritize empathy, innovation, and authentic human engagement. This study contributes to the theoretical discourse by framing competitive advantage as a human endeavor and offers practical implications for service organizations aiming to achieve operational excellence while honoring the human dimensions of service delivery. The integration of strategic, operational, and tactical levels forms a cohesive framework for achieving enduring success through genuine customer relationships and continuous adaptation to evolving market dynamics.